Ultrasound-Guided Percutaneous Peripheral Nerve Stimulation: Neuromodulation of the Sciatic Nerve for Postoperative Analgesia Following Ambulatory Foot Surgery, a Proof-of-Concept Study - Ilfeld, Brian M.; Gabriel, Rodney A; Said, Engy T.; Monahan, Amanda M.; Sztain, Jacklynn F.; Abramson, Wendy B.; Khatibi, Bahareh; Finneran, John J.; Jaeger, Pia T.; Schwartz, Alexandra K.; Ahmed, Sonya S. (Regional anesthesia and pain medicine, 2018)
Background and ObjectivesPercutaneous peripheral nerve stimulation (PNS) is an analgesic modality involving the insertion of a lead through an introducing needle followed by the delivery of electric current. This modality has been reported to treat chronic pain as well as postoperative pain the day following knee surgery. However, it remains unknown if this analgesic technique may be used in ambulatory subjects following foot procedures beginning within the recovery room immediately following surgery, and with only short series of patients reported to date, the only available data are derived from strictly observational studies. The purposes of this proof-of-concept study were to demonstrate the feasibility of using percutaneous sciatic nerve PNS to treat postoperative pain following ambulatory foot surgery in the immediate postoperative period and provide the first available data from a randomized controlled study design to provide evidence of analgesic effect.MethodsPreoperatively, an electrical lead (SPRINT; SPR Therapeutics, Inc, Cleveland, Ohio) was percutaneously inserted posterior to the sciatic nerve between the subgluteal region and bifurcation with ultrasound guidance. Following hallux valgus osteotomy, subjects received 5 minutes of either stimulation or sham in a randomized, double-masked fashion followed by a 5-minute crossover period and then continuous stimulation until lead removal on postoperative days 14 to 28.ResultsDuring the initial 5-minute treatment period, subjects randomized to stimulation (n = 4) experienced a downward trajectory in their pain over the 5 minutes of treatment, whereas those receiving sham (n = 3) reported no such change until their subsequent 5-minute stimulation crossover. During the subsequent 30 minutes of stimulation, pain scores decreased to 52% of baseline (n = 7). Three subjects (43%) used a continuous popliteal nerve block for rescue analgesia during postoperative days 0 to 3. Overall, resting and dynamic pain scores averaged less than 1 on the numeric rating scale, and opioid use averaged less than 1 tablet daily with active stimulation. One lead dislodged, 2 fractured during use, and 1 fractured during intentional withdrawal.ConclusionsThis proof-of-concept study demonstrates that percutaneous sciatic nerve PNS is feasible for ambulatory foot surgery and suggests that this modality provides analgesia and decreases opioid requirements following hallux valgus procedures. However, lead dislodgement and fracture are concerns.Clinical Trial RegistrationThis study was registered at Clinicaltrials.gov, identifier NCT02898103.